OPTIMALISASI PEMBELAJARAN BERBASIS PENGALAMAN (EXPERIENTIAL LEARNING) - Dr. Rosidin (El-QUDWAH, 2014)
Oleh : Rosidin Dosen Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Maulana Malik Ibrahim  Abstract Focus of this article discusses: 1) The study is the result of research normative Tarbawi thematic interpretation of the verses of the Koran that are relevant to the experience -based learning; 2 ) The study discusses the theoretical one experience-based learning model , Experiential Learning (EL) model Kolb; 3 ) Study of practical ideas that shape is constructed from the study of normative and theoretical results , accompanied by bid operational measures at the level applicable . The formulation of this problem is qualitatively assessed in the library research. The results of the study are: 1) The story of the Prophet and the Koran figures indicate explicitly or implicitly the existence of interaction-based learning experience; 2) Theory-based learning experiences that have been tested and are widely applicable theory of Experiential Learning (EL) model Kolb serves three main products, namely (a) EL cycle consisting of experiences (Concrete Experience), Reflective Observation (Reflective Observation), Abstract conceptualization (Abstract conceptualization) and Active Experimentation (Active Experimentation ); (b) learning strategies relevant to EL Cycle; (c) learning style based on EL cycle , namely Divergent , Assimilation, Convergent and Accommodation. 3) Study of practical this study resulted in three recommendations: (a) implementation of the EL Model Cycle Kolb; (b) Model EL-based learning strategies Kolb; (c) Kolb's learning style model facility in learning.